'Becoming-with' a repeat healthy volunteer: Managing and negotiating trust among repeat healthy volunteers in commercial clinical drug trials. (January 2020) - Mwale, Shadreck
Abstract: Recent sociological research has raised important sociological and ethical questions about the role of financial rewards in terms of healthy volunteer involvement in clinical trials. Research suggests that it would be parochial to assume financial rewards alone are sufficient to explain repeat healthy volunteering. This paper explores other factors that might explain repeat healthy volunteering behaviours in phase I clinical drug trials. Drawing on qualitative research with healthy volunteers, the paper argues that while healthy volunteers make rational decisions to take part in drug trials, understanding how they become repeat volunteers requires considering varied relationships and networks involved. Drawing on Deleuze's concept of 'event' and 'becoming-with', the paper illustrates the relational, processual and embodied nature of trust in repeat healthy volunteer involvement in clinical drug trials. The paper concludes that repeat healthy volunteering is a constant flux of negotiating trust and mistrust. The paper contributes to sociological debates about trust and public engagement with technological innovations to illustrate trust among healthy volunteers as processual and changeable. Highlights: Healthy volunteers draw on the consent process and wider networks when considering continued trial participation. Repeat volunteering involves a constant management and negotiation of trust and mistrust. Experience or lack of adverse effects are important for continued participation.